Análise geoestatística de mapas temáticos da produtividade da soja com diferentes grades amostrais - Kestring, Franciele Buss Frescki (2011)
Studies on spatial variability of soybeans yield are of great importance for the development of new technologies that improve the world agricultural production. One of methods that allows this study is geostatistics. The geostatistical analysis makes possible the predictions of results and one of its products are thematic maps. Thus, this trial describes some techniques to draw and compare thematic maps using kriging. The analysis was based on data from soybean yield in t ha−1 according to harvest year 2004/2005 in an experimental area with sampling grades whose distances were: 25x25 m, 50x50 m, 75x75 m and 100x100 m plus a harvest monitor. The maps were compared using error matrix and confusion matrix. In addition, there was a better accuracy of the spatial variability maps that were drawn, while the analysis of coefficients of accuracy allows a better planning of sampling mesh for future studies. The measures of accuracy that were obtained by error matrix are significant options to make comparison among thematic maps, once they provide global indices and also by classes.